Coupling phytoremediation efficiency and detoxification to assess the role of P in the Cu tolerant Ricinus communis L. (May 2020) - Zhou, Xiupei; Wang, Sheliang; Liu, Yonghong; Huang, Guoyong; Yao, Shiyuan; Hu, Hongqing
Abstract: Phosphorous (P) fertilization is an important agronomic practice, but its role in enhancing phytoremediation efficacy and mediating detoxification has rarely been reported in environmental remediation studies. In this study, a pot experiment was undertaken to assess: firstly, the effect of P on phytoextraction of Cu by Ricinus communis L.; secondly, the potential mechanisms by differentiating the effects of the plant from that of P fertilizer (Ca(H2 PO4 )2 ); and thirdly, the role of P in physiological detoxification. Results showed that the application of P fertilizer significantly (p ≤ 0.05) increased the plant biomass as well as the Cu concentrations in plant tissues. This enhanced the phytoremediation efficiency represented by the total Cu extraction (up to 121.3 μg Cu plant −1 ). Phosphorous (P) fertilizer led to a negligible decline in soil pH (0.2 units) but significantly (p ≤ 0.05) reduced the concentrations of soil available in Cu and Fe, due to the formation of insoluble Cu/Fe-phosphate precipitates. Nevertheless, P fertilizer still improved the accumulation and extraction of Cu by R. communis, most likely attributable to the Fe-deficiency induced by applied P fertilizer. Moreover, the application of P fertilizer revealed a significant reduction in MDA, and a profound (p ≤ 0.05) elevation in the amount of photosynthetic pigments, GSH and AsA, along with the enhanced activities of antioxidative enzymes (SOD, POD, and CAT). In this way, Cu toxicity was alleviated. P fertilizers not only enhance the phytoremediation efficiency of Cu-contaminated soils by R. communis, but they also facilitate detoxification, which improves our understanding of the role of P in phytoremediation technologies. Highlights: P fertilizer significantly increased the plant biomass and the Cu concentrations in plant tissues. P fertilizer hardly affected the soil pH but significantly decreased the concentrations of soil available Cu and Fe. Fe deficiency induced by the application of P fertilizer played an important role in the uptake of Cu by R. communis. P fertilizer effectively alleviated the toxicity via improving the photosynthetic capacity and increasing the antioxidative ability.